2022
DOI: 10.1155/2022/6842530
|View full text |Cite
|
Sign up to set email alerts
|

TMT-Based Quantitative Proteomic Analysis Reveals Downregulation of ITGAL and Syk by the Effects of Cycloastragenol in OVA-Induced Asthmatic Mice

Abstract: Background. Cycloastragenol (CAG) has been reported to alleviate airway inflammation in ovalbumin- (OVA-) induced asthmatic mice. However, its specific mechanisms remain unclear. Objective. This study is aimed at investigating the effects of CAG on asthma, comparing its efficacy with dexamethasone (DEX), and elucidating the mechanism of CAG’s regulation. Methods. The asthma mouse model was induced by OVA. CAG at the optimal dose of 125 mg/kg was given every day from day 0 for 20-day prevention or from day 14 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 62 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…SYK is a kinase that regulates the signal transformation of adaptive immune receptors, increasing ligand affinity for integrin receptors. 27 Prior research has noted the importance of Syk because it not only acts as an inflammatory mediator, but also participates in airway wall remodeling in asthma. In addition, Syk inhibition diminishes pulmonary airway inflammation and M1 polarization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SYK is a kinase that regulates the signal transformation of adaptive immune receptors, increasing ligand affinity for integrin receptors. 27 Prior research has noted the importance of Syk because it not only acts as an inflammatory mediator, but also participates in airway wall remodeling in asthma. In addition, Syk inhibition diminishes pulmonary airway inflammation and M1 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…After tracheostomized, mice were intubated and connected to the Fine Pointe Resistance and Compliance system (DSI Buxco Electronics, Saint Paul, MN, USA). To detect lung function, mice were exposed to Mch at increasing doses of 0, 6.25, 12.5 and 25 mg/ml after stable breathing 27 . Airway resistance ( R L ) and lung dynamic compliance (Cdyn) were obtained and analyzed by FinePointe data acquisition and analysis software (DSI Buxco Electronics).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] The previous study has demonstrated that intraperitoneal injection of OVA and alum once a week for 2 weeks is the most straightforward and effective approach to induce an asthmatic reaction in mice. 11 However, the inconsistent use of sensitizing OVA doses in current studies [12][13][14] and the lack of research on their effect on AHR necessitate further investigation. Therefore, we conducted a study using increasing doses (0, 10, 20, 50, and 100 μg) of sensitizing OVA in a BALB/c murine model of asthma to evaluate their impact on AHR to methacholine (MCh), as well as histological changes, eosinophilic infiltration, and epithelial damage.…”
Section: Introductionmentioning
confidence: 99%